63 Post-concussion syndrome (PCS): parent and youth experience with school and ongoing concussion symptoms. (9th June 2015) - Selci, Erin; Chu, Stephanie; Ellis, Michael; Ritchie, Lesley; Russell, Kelly
Abstract : Statement of purpose: Post-concussion syndrome (PCS) refers to symptoms that last more than one month after a concussion, which increases the risk for anxiety, depression and poor academic performance. Our objective was to examine how parents and youth cope with persistent concussion symptoms and navigating the school system after diagnosis of PCS. Methods/approach: Two focus groups were conducted: one with youth who developed PCS and one with their parents. A semi-structured interview including questions regarding concussion symptoms and academic experiences and accommodations was administered. Interviews were audio-recorded, transcribed, and analysed to identify themes. Results: Parent (n = 6) and youth (n = 6) focus groups identified three common themes: (1) a need for the school system to have increased understanding of PCS and improved academic accommodations for these students; (2) PCS was associated with mental health complications (e.g., feelings of isolation) and pressure upon returning to school; and (3) parental frustration associated with managing return to learn expectations and their child's recovery. Two contrasting themes between parent and youth groups emerged. First, parents experienced guilt because they questioned if their child exaggerated symptoms verse youth report of only lying about feeling better to return to everyday activities. Second, parents and youth differed on whether the youth felt bullied. Conclusions: PCS youth face challenges when returning to school and expressed a desire for increased academic understanding/accommodation. This is attainable through increased awareness and education in the schools. To improve parent and youth mental health during recovery from PCS, support groups may aide to decrease feelings of isolation and frustration. Significance and contributions: The findings bring attention for improved PCS education in the school system, as well as the need for community support of families who have a child diagnosed with PCS.